Unilateral and bilateral load-velocity relationships in athletes: evidence from a study in boxers - Han, Y.; Xie, Y.; Niu, Z.; Jia, J.; Zhang, Z. (Frontiers in Sports and Active Living, 2025)
Objective: This study aimed to investigate the load-velocity (L-V) relationship in boxers during unilateral (Bulgarian split-squat, BSS) and bilateral (back-squat, BS) lower-limb exercises, and to compare the mean velocity (MV) outputs between these two modalities, with the ultimate goal of providing an evidence-based foundation for optimizing strength training in boxing.